Theoretical Study of the Turbulent Combustion of Nitramine Propellant. Issue 7 (3rd July 2017) - Bray, Kenneth N. C.; Champion, Michel; Libby, Paul A.
ABSTRACT: Our analysis of the burning of nitramine propellant in a turbulent shear flow involves several preparatory considerations, their development, and subsequent implementation. Involved are the thermochemistry and chemical kinetics of nitramine combustion, a flow model, and a turbulence model. Li and Williams (1996) provide a reduced mechanism for nitramine combustion, one appropriate for incorporation in a turbulent flow analysis. Our fluid mechanical model consists of simple shear flow with a specified thickness and a specified velocity and turbulent intensity in its external stream. The chemical composition of this external stream consists of the complete first stageof the combustion of nitramine. Given the overall complexity of the system, we adopt the model of turbulence rather than a more complete Reynolds stress model. A key parameter in the equations resulting from these considerations is a Reynolds number based on conditions in the external stream and on the shear layer thickness. We exploit the large magnitude of this number in flows of applied interest and carry out an asymptotic analysis. As in related analyses the shear layer is found to involve a two-layer structure: a thin layer which is adjacent to the nitramine surface and in which molecular and turbulent transport exchange dominance, and a thick outer layer involving only turbulent transport. A significant finding from the asymptotic analysis is that combustion of the products of the devolitization of nitramine is confined to the thin inner layer. There are several important consequences of this finding. A parameter relating the characteristic flow and chemical times is determined by the solution for the inner layer. The outer layer involves no combustion and constant density. Since mass transfer is involved, the asymptotic analysis exposes the significant effect of mass transfer on the usual log-law behavior of the mean velocity at the outer edge of the wall layer. Solutions are given for the inner layer for four pairs of values for the two parameters determining the rate of nitramine consumption and the turbulent intensity in the external flow. The outer layer is then described through a representative solution of the corresponding equations. Moreover, an elegant solution for the combustion in the case of laminar flow is presented.